О субсидировании государством процесса создания объектов интеллектуальной собственности при разработке программ развития транспорта - Mikhail Yuryevich Alekhin (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
This article is devoted to increasing innovation, investment and economic competitiveness of the Russian Federation in the light of experience of the leading world countries, particularly the United States. The need to improve legislative procedures and public policy in the sphere of creation of intellectual property, by subsidizing the budget and securing the rights for the scientific and tech nical results. The solution is only possible with a clear understanding of the economic and political goals of the country’s strategic and operational motives competitors and tools, which should be created (can be copied in part) for the adequate management (adequate challenges) studied management process. To determine the effect of the innovation activity in the economies and their competitiveness will consider approaches to the study of competitiveness and define at what stage of the historical development of economic theory, there was a discussion on the relationship between scientific and technological progress, competitiveness and well-being of the country, as well as carry out the analysis of the major scientific papers on this issue.